Analysis of the Fatigue Damage Behavior of AW2099-T83 Al-Li Alloy under Strain-Controlled Fatigue - Muhammed Jamiu Adinoyi; Nesar Merah; Jafar Albinmousa (Fracture and Structural Integrity, 2019)
Microstructural characteristics, monotonic and strain-controlled cyclic axial behaviors of AW2099-T83 Aluminum-Lithium alloy were investigated. Grain sizes and structures are not uniform in the different orientations studied. High strength and low ductility characterize the tensile behavior of the alloy under static loading. Strain-controlled fatigue testing was conducted at strain amplitudes ranging from 0.3% to 0.7%. Over this range, macro plastic deformation was only observed at 0.7%.  Cyclic stress evolution was found to be dependent on both the applied strain amplitude and the number of cycles. Limited strain hardening was observed at low number of cycles, followed by softening, due probably to damage initiation. With low plastic strain, analytical approach was adopted to profile the damaging mechanism for the different applied strain amplitude. Because of the absence of fatigue ductility parameters due to low plasticity, a three-parameter equation was used to correlate fatigue life. Fractured specimens were studied under SEM to characterize the fracture surface and determine the controlling fracture mechanisms. The fractography analysis revealed that fracture at low strain amplitudes was shear controlled while multiple secondary cracks were observed at high strain amplitude. Intergranular failure was found to be the dominant crack propagation mode.